To evaluate the effect of consuming soy products on the rate of fall in serum oestragen level in post TAHBSO women on oestrogen implant. - Vahid Bossaghzadeh; Norzilawati Mohd Naim; Yulianty Ariffuddin; Zainul Rashid Mohd Razi (Department of Surgery, UKM Medical Centre, 2014)
This was a prospective comparative study which was undertaken from January, 2008 to May, 2012. A total of 35 women, who had undergone TAHBSO for benign gynaecological conditions, were each inserted with a 50 mg oestradiol implant in the sub-rectus space intra-operatively. Serum oestradiol levels were measured on a two-monthly basis until the level fell below 50 pmol/litre and the patients have developed post-menopausal symptoms. A second 50 mg oestradiol implant was then inserted as out-patients in either of the lumbar region of the abdomen using a special trocar. These patients were then advised to consume at least one glass of soya products every day. Serum oestradiol levels were again measured on a two-monthly basis until the level fell below 50 pmol/litre and the patients have developed post-menopausal symptoms. The means of each two monthly intervals were compared using the comparisons of means to determine whether there was any difference in the rate of fall of the oestrogen levels with or without soy product intake.